The role of tumor-infiltrating lymphocytes in triple-negative breast cancer and the research progress of adoptive cell therapy - Li, Ruonan; Cao, Lili (Frontiers in Immunology, 2023)
The treatment outcome of breast cancer is closely related to estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) expression. Triple-negative breast cancer (TNBC) lacking ER, PR, and HER2 expression has limited treatment options and a poor prognosis. Tumor-infiltrating lymphocytes (TILs) play a role in promoting or resisting tumors by affecting the tumor microenvironment and are known as key regulators in breast cancer progression. However, treatments for TNBC (e.g., surgery, chemotherapy and radiotherapy) have non-satisfaction's curative effect so far. This article reviews the role of different types of TILs in TNBC and the research progress of adoptive cell therapy, aiming to provide new therapeutic approaches for TNBC.